Revisiting ISO 14000 Diffusion: A New “Look” at the Drivers of Certification - Vastag, Gyula (Production and Operations Management, 2004)
This replication study of the drivers of ISO 14000 certifications extends the work of Corbett and Kirsch (2001) and provides a different and simpler predictive model of the factors contributing to the growth of ISO 14000 certifications. The main finding is that at national level ISO 14000 certification densities can be explained by two factors: the installed base of ISO 9000 certificates and the number of environmental treaties signed and ratified. The first factor, considering the common elements of the two standards, points to conditions of infrastructural convenience, while the second highlights the importance of political‐economic considerations. The study uses a new set of tools (graphical displays, distribution‐free computer intensive methods) that are better suited for exploratory research when discontinuities and existence of subgroups in the data set may make findings from a linear regression suspect.